INTERNATIONAL CONFERENCE "RELIGIOUS INSTITUTIONS AND PRACTICES DURING THE COVID PANDEMIC: CHALLENGES AND ANSWERS» - Yerekesheva, L.G. (Journal of Oriental Studies, 2022)
On April 15, 2021, the international online conference "Religious Institutions and practice during the COVID pandemic: challenges and responses”. The conference was held in within the framework of the project "Religious institutions and practice in the context of digitalization and change social space during the COVID pandemic in Kazakhstan" (GF MES RK 2020-2021, IRN AP08956706, project leader L.G. Erekesheva, Doctor of History, Faculty of Oriental Studies Kazakh National University named after al-Farabi (KazNU named after al-Farabi).